Elaboración de una galleta a partir de la mezcla de harinas de granos andinos del Ecuador quinua (Chenopodium quinoa) y amaranto (Amaranthus) - Feijoo Zozoranga, Edwin Lenin (2025)
The study focused on developing a cookie using a flour blend made from Andean grains from Ecuador, such as quinoa and amaranth. The research employed a quantitative approach, conducting a proximate product analysis and selecting the best formulation through a sensory analysis. First, four flour formulations were prepared, varying the amounts of quinoa and amaranth, and the best formulation was selected through a consumer-oriented sensory analysis. The sensory analysis included an acceptability evaluation using a 9-point hedonic scale. Based on the four formulations, cookies were made, and their acceptability was analyzed. The winning formulation was sample 2, which consisted of 75% quinoa flour and 25% amaranth flour. This result demonstrated that the cookies obtained with this formulation provided highly acceptable organoleptic characteristics for consumers of this type of food. The proximate analysis of the cookie resulted in 9.69% protein, 5.47% fiber, 3.20% moisture, 14.3% fat, and 1.44% ash. These findings suggest that cookies are a good source of essential nutrients, and the combination of quinoa and amaranth flour enhances the product's nutritional value and organoleptic properties. This research supports the idea that a blend of quinoa and amaranth flour can improve the nutritional quality of widely consumed baked goods like cookies. It may also meet current market demands for highly nutritious products.